Respuesta reproductiva de ovejas nulíparas expuestas a carneros tratados con selenio más vitamina E - Veliz-Deras, Francisco Gerardo; Montes Rosales, Lorena Marlene; Gaytán-Alemán, Leticia Romana; Ángel-García, Oscar (Ecosistemas y Recursos Agropecuarios, 2023)
The reproductive response of nulliparous-anovulatory Dor- per ewes exposed to rams treated with selenium (Se) plus vitamin E(Vit. E) was evaluated. A first of rams was treated (GT; n=5) with 1 mg of Se plus 70 IU of Vit. E x every 10 kg of LW via IM, and a second group, control (GC; n=5) with 1 mL of saline solution, both treatments were applied every 7 days x 28 days. At the end of the treatments, the groups of rams were placed in contact with two groups of females (n = 17 each), and the appetitive (CSA) and consummatory (CSC) sexual behavior of the rams was recorded. The reproductive response of ewes exposed to males was similar (P > 0.05) in both treatments. Treatment with Se plus Vit. E did not stimulate the sexual behavior of the rams and therefore the reproductive response of the ewes was not enhanced.